2018
DOI: 10.1097/pcc.0000000000001756
|View full text |Cite
|
Sign up to set email alerts
|

Duration and Time Trends in Hospital Stay for Very Preterm Infants Differ Across European Regions*

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 37 publications
2
34
3
2
Order By: Relevance
“…14 Also, a multicentre study carried out in the European region also documented an increased mean LOS of 106.7 days and 105.2 days for infants delivered at 23 weeks and 24 weeks gestation respectively as compared with 42.7 days for infants delivered at 31 weeks gestation. 15 This is not surprising as the duration of hospital stay has been observed to be inversely proportional to the gestational age due to associated medical conditions observed especially in these preterms with decreased gestational age thus requiring a longer hospital stay. 7,15,16 The length of stay of preterm babies admitted in neonatal units vary dramatically as observed in the present study where babies delivered at 24 weeks gestational age had a mean LOS of 62.00±0.00 days which was much shorter than the mean LOS of 120.70 days reported in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 96%
“…14 Also, a multicentre study carried out in the European region also documented an increased mean LOS of 106.7 days and 105.2 days for infants delivered at 23 weeks and 24 weeks gestation respectively as compared with 42.7 days for infants delivered at 31 weeks gestation. 15 This is not surprising as the duration of hospital stay has been observed to be inversely proportional to the gestational age due to associated medical conditions observed especially in these preterms with decreased gestational age thus requiring a longer hospital stay. 7,15,16 The length of stay of preterm babies admitted in neonatal units vary dramatically as observed in the present study where babies delivered at 24 weeks gestational age had a mean LOS of 62.00±0.00 days which was much shorter than the mean LOS of 120.70 days reported in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 96%
“…Our study shows that during hospitalization, preterm neonates with good nutritional status were decreased from 159 (83.68%) to 104 (54.75%), and undernourished neonates were increased from 31 (16.32%) to 86 (45.36%) at discharge. Compared to another study by Fenton in 2013, in Calgary, Regina and San Diego found the number of undernourished neonates was increased from 11% to 31% after two weeks of hospitalization (Fenton et al, 2013;Hintz et al, 2010;Lee et al, 2018;Maier et al, 2018). The inadequate improvement of nutritional status in the preterm neonates due to multifactorial, including nutritional support during treatment, the morbidity of preterm neonates, and complex interactions of genetic and environmental (Martins-Celeni et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, we observed an unusually high proportion of unplanned use of health services in the month after discharge. Our sample included mostly European, married, and highly educated women, which corresponds to sociodemographics of parents in other European reports 29,30 . Their overall discharge readiness scores indicated that they felt ready for discharge overall, which is congruent with the current scientific literature 2,31 .…”
Section: Discussionmentioning
confidence: 99%